Chronic pelvic pain in women. Issue 999 (24th February 2009) - Vincent, K
Abstract : Chronic pelvic pain is a major public health problem for women throughout the developed world. The complex innervation of the pelvis and the anatomical proximity of pelvic viscera mean this symptom frequently overlaps traditional medical specialties, leading to diagnostic delay and frequently inadequate treatment. Careful history taking and examination can in itself be therapeutic and will likely identify a number of causal and perpetuating factors which should be managed within the context of a multidisciplinary clinic.